2021
DOI: 10.1002/mnfr.202000365
|View full text |Cite
|
Sign up to set email alerts
|

Protein Isolates from Raw and Cooked Foxtail Millet Attenuate Development of Type 2 Diabetes in Streptozotocin‐Induced Diabetic Mice

Abstract: Scope Millet protein has received much attention due to its beneficial role in alleviating metabolic disease symptoms. This study aims to investigate the role and molecular mechanism of foxtail millet protein isolates, including protein isolates from raw and cooked foxtail millet in alleviating diabetes, including gut microbiota and intracellular signal pathways. Methods and results Protein isolates from raw and cooked foxtail millet are orally administered to streptozotocin (STZ)‐induced diabetic mice for 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…142 Recent studies demonstrated that protein extracts from foxtail millet attenuated insulin resistance in HFD/STZ-induced diabetic mice by modulating gut microbiota composition and the GLP-1 receptor (GLP-1R)/PI3K/AKT pathway. 143 Strikingly, total glycosides from R. glutinosa leaves could reduce FBG and alleviate renal damage in db/db mice. 144 Compared with control group, db/db mice exhibited higher abundance of Acetatifactor and Bacteroidales_S24-7 and lower abundance of Roseburia and Erysipelotrichaceae, while R. glutinosa leaf total glycosides could reverse these changes.…”
Section: Microbiota In Dmmentioning
confidence: 98%
See 1 more Smart Citation
“…142 Recent studies demonstrated that protein extracts from foxtail millet attenuated insulin resistance in HFD/STZ-induced diabetic mice by modulating gut microbiota composition and the GLP-1 receptor (GLP-1R)/PI3K/AKT pathway. 143 Strikingly, total glycosides from R. glutinosa leaves could reduce FBG and alleviate renal damage in db/db mice. 144 Compared with control group, db/db mice exhibited higher abundance of Acetatifactor and Bacteroidales_S24-7 and lower abundance of Roseburia and Erysipelotrichaceae, while R. glutinosa leaf total glycosides could reverse these changes.…”
Section: Microbiota In Dmmentioning
confidence: 98%
“…Alginate from S. fusiforme not only significantly regulated the abundance of bacterial taxa such as Lactobacillus , Enterorhabdus , Turicibacter , and Helicobacter but also reduced the levels of metabolite branched-chain amino acids and aromatic amino acids in the colon, thereby improving glycolipid metabolism and oxidative stress in T2DM mice . Recent studies demonstrated that protein extracts from foxtail millet attenuated insulin resistance in HFD/STZ-induced diabetic mice by modulating gut microbiota composition and the GLP-1 receptor (GLP-1R)/PI3K/AKT pathway . Strikingly, total glycosides from R. glutinosa leaves could reduce FBG and alleviate renal damage in db / db mice .…”
Section: Natural Products Targeting the Gut Microbiota In Dmmentioning
confidence: 99%
“…Most amino acids of sample 4 were higher than sample 2, probably due to differences in thermal efficiency, proving the importance of processing parameters. Fu’s research has demonstrated that cooking can induce the formation of disulfide bonds and hydrophobic aggregates, as well as changes in protein secondary structure (transitions between α -helix, β -sheet, β -turn), giving millet a higher amino acid content and in vitro protein digestibility, thereby producing more bioactive amino acids or peptides during intestinal digestion, participating in the regulation of glucose metabolism and improving blood sugar levels [ 47 ]. However, some studies have also shown that the in vitro protein digestibility of millet is significantly reduced after high pressure steam treatment, mainly due to protein denaturation, reduced protein resistance to enzymes, and protein-other interactions [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most peptides contained 40% hydrophobic residues) Increase glucose uptake, reduction in glycated haemoglobin (HbA1c) levels reducing fasting glucose Human skeletal muscle cells, db/db diabetic mice , and clinical (double-blinded, placebo controlled human trial) Chauhan et al (2021 ) Foxtail millet protein Raw and cooked protein isolates Not determined Hypoglycemic effects through rewiring glucose homeostasis, mitigating diabetes-induced gut dysbiosis. The cooked foxtail millet protein isolate affected the GLP-1R/PI3K/AKT pathway and reversed the weight loss trend and alleviated lipid disorders in diabetic mice STZ-induced diabetic mice Fu et al (2021 ) Wheat gluten Commercial protein hydrolysate (HyPep 4601) Not determined Suppression of food intake in healthy rats, elevating plasma PYY levels, stimulation of CCK and GLP-1 in enteroendocrine cells Enteroendocrine cell lines (STC-1 cells and GLUTag cells), and Wistar rats Chen, Hira, Nakajima, and Hara (2018 ) Walnut Neutrase and alcalase LVRL, LRYL, VLLALVLLR Improve glucose consumption, glucose uptake, and GLUT4 translocation, elevation of p-IRS-1 and p-Akt. Inhibition of glucose-induced insulin resistance by activating IRS-1/PI3K/Akt and Nrf2/HO-1 signaling pathways HepG2 cells Wang et al (2020b ) Walnut Alcalase LPLLR α-glucosidase and α-amylase inhibition, improving hepatic insulin resistance, increase glycogen synthesis and glucose uptake, decrease gluconeogenesis via activating the IRS-1/PI3K/Akt and AMPK signal pathways Glucose induced insulin resistant HepG2 cells Wang et al (2020a ) Walnut Neutrase and alcalase Peptide fractions with 3–10 KDa α-glucosidase inhibition, increase in extracellular glucose consumption, reduce fasting blood glucose, increase in insulin secretion, liver glucokinase and glycogen levels Insulin-resistant HepG2 cells, STZ-induced diabetic mice Wang et al (2018 ) Egg white protein Thermolysin and pepsin WEKAFKDED, QAMPFRVTEQE, ERYPIL, VFKGL Enhance pre-adipocyte differentiation, show insulin mimetic and sensitizing effects (Akt and ERK1/2 phosphorylation), improve glucose uptake, glucose tolerance, and reduce systemic inflammation, reduce adipocyte size and increased PPARγ2 protein abundance and activity 3T3-F442A pre-adipocytes and diet-induced insulin resistant rats …”
Section: Antidiabetic Potential Of Bioactive Peptidesmentioning
confidence: 97%